Neonatal cerebral infarction diagnosed by diffusion-weighted MRI: pseudonormalization occurs early. - Mader, I; Schöning, M; Klose, U; Küker, W (2002)
BACKGROUND: Seizures in the neonatal period may be the single symptom of acute ischemic cerebral infarction. It may be difficult to establish the diagnosis in the acute phase by the use of ultrasound, CT, and conventional MRI because of the high water content of the immature brain. Diffusion-weighted (DW) MRI is a very sensitive and fast imaging modality to visualize acute ischemic stroke in infants even before conventional MR images become abnormal. Signal abnormality in DW MRI, however, seems to follow a different time course than in older patients. CASE DESCRIPTION: DW MRI became falsely negative 1 week after stroke (pseudonormalization) in 2 newborn patients during persistence of signal abnormalities on turbo spin-echo images, whereas the so-called pseudonormalization in adults normally occurs within 10 to 14 days. CONCLUSIONS: T2-weighted sequences should supplement DW images to reliably detect subacute ischemic infarctions in the neonatal period.